2018
DOI: 10.21873/invivo.11409
|View full text |Cite
|
Sign up to set email alerts
|

Spleen Dose–Volume Parameters as a Predictor of Treatment-related Lymphopenia During Definitive Chemoradiotherapy for Esophageal Cancer

Abstract: Aim: Our study sought to identify dosimetric predictors of treatment-related lymphopenia during chemoradiotherapy for esophageal cancer. Materials and Methods: Patients with esophageal cancer who had received definitive chemoradiotherapy at our Institution were retrospectively assessed. The absolute volume of the spleen, body, and bone marrow that had received 5, 10, 20, and 30 Gy and the mean splenic dose were recorded. Results: Multivariate linear regression analysis revealed that docetaxel use and spleen do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 21 publications
(6 reference statements)
0
30
0
Order By: Relevance
“…Nevertheless, the mechanisms responsible for RIL remain unclear. Lymphoid organ radiation, including bone marrow, thymus, spleen, and lymph nodes, could likely contribute to RIL (22)(23)(24). Radiation can directly damage hematopoietic stem cells in bone marrow or mature lymphocytes in lymphoid tissues, as well as stimulate the secretion of immunosuppressive cytokines, promoting immunosuppression (25).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the mechanisms responsible for RIL remain unclear. Lymphoid organ radiation, including bone marrow, thymus, spleen, and lymph nodes, could likely contribute to RIL (22)(23)(24). Radiation can directly damage hematopoietic stem cells in bone marrow or mature lymphocytes in lymphoid tissues, as well as stimulate the secretion of immunosuppressive cytokines, promoting immunosuppression (25).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas most studies demonstrate RIL as a poor prognostic factor in cancer treatment outcomes, the direct correlation between dose to lymphocyte-rich organs and RIL has been most recently described in pancreatic cancer patients receiving unintentional splenic RT and esophageal cancer patients receiving unintentional cardiac and splenic RT 10,17,18 . Using irradiation of these two lymphocyte-rich organs as our model system for RIL, we studied the potential normal tissue sparing ability of ultra-high dose rate RT.…”
Section: Introductionmentioning
confidence: 99%
“…As both lung cancers and esophageal cancers are mainly located within the thoracic region, we believe that the EDIC formula would be a valid model in esophageal cancer too. On the other hand, Saito et al 22 found that splenic dose volumes but not bone marrow dose volumes were predictive in treatment-related lymphopenia during chemoradiotherapy for esophageal cancer. We believe future studies can incorporate dose to the spleen as a better estimate of dose to EDIC.…”
Section: Discussionmentioning
confidence: 99%